RANCANG BANGUN SISTEM PENGAMANAN IKAN DI KERAMBA APUNG LEPAS PANTAI MENGGUNAKAN SENSOR PASSIVE INFRARED - Misbahuddin Yafi Ramadhani; Akhmad Zainuri; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2023)
In floating cage cultivation, security is one of the important aspects to be considered. Possible threats include fish theft, theft of cultivation equipment, predator attacks such as birds or predatory fish. The importance of security devices against fish thieves in floating cages on Gili Ketapang Island cannot be underestimated. In an effort to protect and maintain the sustainability of fish farming, the use of effective security devices is essential. By installing security devices such as suspected movement detection, notification delivery, and sirens, cage owners can increase the likelihood of detection and prevent acts of fish theft. These devices provide better surveillance and allow cage owners to respond quickly in case of suspicious behavior. To prevent fish theft in floating cages, research was conducted to design a cage security system. An effective security system can help identify and prevent theft or attacks on floating cages, improve supervision, and provide a sense of security to cage owners. In this final research project, we will analyze the performance of ESP32 Cam in sending images, analyze the performance of SIM800l module in making calls and power consumption in the security system of fish theft in floating cages. The implementation results obtained that the security system using a 17Ah LifePO4 battery was able to be active for 12 hours in standby conditions with a total power of 2.88W and in a state of detecting movement the system was able to be active for 2.5 hours with a total power of 35.96W. In this study, a security system was designed for monitoring cages remotely using ESP32 Cam using telegram bot assistance, for motion detection using the SIM800l module with PIR sensor as object detector and triggering the SIM800l module to make a call. The results of this study are that for monitoring, ten tests were carried out and had a success percentage of 90%, for motion detection it had a success rate of 80% by conducting ten tests. Keywords : security system, battery life, image processing, motion detection.